When nation building is at odds with economic reform and EU membership - Johannsen, Lars; Hilmer Pedersen, Karin (2009)
Abstract: While small state logic and the imperative of a return to Europe by and large explain why the stringent EU requirements were adopted by the candidate countries prior to membership it, is not suffi cient to explain why they did so to varying degree and at different speeds. Through a comparative analysis of four countries, it is argued that different choices in nation-building affected the countries’ capacity to handle large-scale reforms resulting, in a ‘go-go’ process in the Czech Republic and Estonia and a ‘stop-go’ process in Slovakia and Latvia. Consequently, at present, as membership of the European Union is well underway, Slovakia and Latvia have already had their nation building discussions. The pending question is what the political consequences will be in the Czech Republic and Estonia if and when nation building finds its way back to the political arena